Dat's ain't the language I've learned : como a variação linguística é apresentada nos livros didáticos de cursos de franquia destinados ao ensino de inglês - Melo, Michéle Muliterno de (2008)
This research had as main goal to investigate if some language variations in English are presented in the Language School’s class material and, in affirmative case, how it is accost and what kind of variation appears in those material. To do so, two Language Schools were selected. The first one – called School A- with audio lingual approach and the other – School B - with the communicative approach. These schools are representative throughout the country, with the material and a questionnaire answered by the Language School coordinator’s analyses was possible to enquire the main goal of this research. After the analyses it was verified that the linguistic variation is approached in both the courses, each one in a different way.